Awareness and perception of heart failure among European cardiologists, internists, geriatricians, and primary care physicians. - Remme, W; McMurray, J; Hobbs, F; Cohen-Solal, A; Lopez-Sendon, J; Boccanelli, A; Zannad, F; Rauch, B; Keukelaar, K; Macarie, C; Ruzyllo, W; Cline, C (2008)
AIMS: To assess awareness of heart failure (HF) management recommendations in Europe among cardiologists (C), internists and geriatricians (I/G), and primary care physicians (PCPs). METHODS AND RESULTS: The Study group on HF Awareness and Perception in Europe (SHAPE) surveyed randomly selected C (2041), I/G (1881), and PCP (2965) in France, Germany, Italy, the Netherlands, Poland, Romania, Spain, Sweden, and the UK. Each physician completed a 32-item questionnaire about the diagnosis and treatment of HF (left ventricular ejection fraction <40%). This report provides an analysis of HF awareness among C, I/G, and PCP. Seventy-one per cent I/G and 92% C use echocardiography, and 43% I/G and 82% C use echo-Doppler as a routine diagnostic test (both P < 0.0001). In contrast, 75% PCP use signs and symptoms to diagnose HF. Fewer I/G would use an angiotensin-converting enzyme (ACE)-inhibitor in >90% of their patients (64 vs. 82% C, P < 0.0001), whereas only 47% PCP would routinely prescribe an ACE-inhibitor. Worsening HF was considered a risk of ACE-inhibitor therapy by 35% PCP. I/G and PCP consistently do not prescribe target ACE-inhibitor doses (P < 0.0001 vs. C). Only 39% I/G would use a beta-blocker in >50% of their patients (vs. 73% C, P < 0.0001). Also, only 5% PCP would always, and 35% often, prescribe a beta-blocker and reach target doses in only 7-29%. Moreover, 34% PCP and 26% I/G vs. 11% C (P < 0.0001) do not start a beta-blocker in patients with mild HF, who are already on an ACE-inhibitor and are on diuretic. In mild, stable HF, 39% PCP and 18% I/G would only prescribe diuretics, vs. 7% C (P < 0.0001). In patients with worsening HF in sinus rhythm and on an optimal ACE-inhibitor, beta-blockade and diuretics, significantly more C would add spironolactone, but I/G would more often add digoxin. CONCLUSION: Although each physician group lacks complete adherence to guideline-recommended management strategies, these are used significantly less well by I, G, and PCPs, indicating the need for education of these essential healthcare providers.